2022
DOI: 10.3389/fgwh.2022.832549
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Menstrual Health Knowledge: Awareness of Menstruation at Menarche as an Indicator

Abstract: As initiatives to support menstrual health are implemented globally, monitoring progress through a set of comprehensive indicators provides important feedback to direct policies and programs. One proposed core indicator is awareness of menstruation at menarche. That is, at the time of menarche an adolescent girl knowing that menstrual bleeding is something she will experience. In this investigation, we undertook secondary analysis of data collected across four studies to support interpretation of this indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The amount of information that PWM possess during their first bleeding influences how they experience menarche [ 44 ]. This is consistent with several studies that found that participants felt underprepared and recalled high levels of fear and distress at menarche if they were unaware of menstruation [ 5 , 10 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The amount of information that PWM possess during their first bleeding influences how they experience menarche [ 44 ]. This is consistent with several studies that found that participants felt underprepared and recalled high levels of fear and distress at menarche if they were unaware of menstruation [ 5 , 10 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The average age for menarche in our population was 12.08 years, in line with the range provided by previous studies (11.9—12.1 years) [ 32 ]. Older age at menarche is associated with more information [ 33 ], probably because those who experience menarche later have more time and chances to learn about it. In our study, several respondents who experienced early menarche commented on how they received the information too late and the negative impact this had on how they lived through their first period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 47 In a secondary analysis of four studies assessing awareness of menstruation before menarche among 2317 schoolgirls from Myanmar, Bangladesh and Uganda, and 599 adult women from Uganda, awareness was the lowest in Bangladesh (34%) and highest in Myanmar (84%). 49 Lack of menstrual knowledge among university students from LMICs was associated with negative menstrual experiences throughout reproductive life and might have a negative impact on general health and well-being of girls and women. 20 …”
Section: Discussionmentioning
confidence: 99%